Effect of fixed orthodontic appliances on gingival status and oral microbiota: a pilot study - Marincak Vrankova, Zuzana; Rousi, Margarita; Cvanova, Michaela; Gachová, Daniela; Ruzicka, Filip; Hola, Veronika; Lochman, Jan; Izakovicova Holla, Lydie; Brysova, Alena; Borilova Linhartova, Petra (BMC oral health, 2022)
BACKGROUND: This pilot study aimed to investigate how fixed orthodontic appliances simultaneously applied on the upper and lower arches affect the oral environment in the medium term. METHODS: The oral status of 30 orthodontic patients was evaluated using the number of decay-missing-filled teeth (DMFT), plaque (PI), and gingival indices (GI) before bonding of fixed orthodontic appliances (T0) and during the therapy (T1). Besides, the gingival crevicular fluid (GCF) and a dental plaque were collected. Samples were analyzed for selected Candida sp. and for 10 selected oral bacteria using mass spectroscopy and multiplex polymerase chain reaction, respectively. RESULTS: In 60% of patients, deterioration of the oral status (demonstrated by the increase in PI) was recorded (p < 0.05). Moreover, the changes in PI correlated with those of GI (p < 0.001). At the T1 time point, the mean representation of Actinomyces sp. in the total prokaryotic DNA in GCF and dental plaque of individual patients increased compared to T0 (p < 0.05). The probability of finding any of the 7 selected periodontal bacteria combined with Candida sp. was 10 times higher in patients in whom PI deteriorated between T0 and T1 (p < 0.01). CONCLUSIONS: Changes in the oral microbial diversity and an increase in PI were observed in the medium term after bonding of orthodontic appliance. Our study highlights the importance of a complex approach in this type of research as the association between clinical characteristics and combined microbial parameters is higher than when evaluated separately.
Keywords: zubní plak; mikrobiota; Dental Plaque; Candida; lidé; Orthodontic Appliances; pilotní projekty; Pilot Projects; Humans; fixní ortodontický aparát; ortodontické aparáty; indexy plaku; Orthodontic Appliances, Fixed; Dental Plaque Index; Microbiota